The development of a clinical management pathway for chest wall pain in elite rowers - Hooper, I.; Blanch, P.; Sternfeldt, J. (Journal of Science and Medicine in Sport, 2011)
Introduction: Chest wall pain continues to be a significant problem in elite rowing, generating substantial loss of training time. Typically chest wall pain can originate from bony (i.e. stress fractures) and non bony structures. Non bony causes of chest wall pain include the costo-chondral joints, intercostals, fascia and thoracic referral. Failing to diagnose a bony cause of chest wall pain early may allow an athlete to continue training, potentially making the stress reaction or stress fracture worse. Conversely, late diagnosis of a non-bony pathology may lead to time removed from training that is not necessary. Methods: Rowing Australia has an injury surveillance system in operation across all SIS/SAS scholarship holders. This system enables the capture of diagnosis, causes and time lost from training for all injuries. Results: During the 2009 & 2010 domestic and international seasons, amongst elite rowers across Australia, there were 28 cases of chest wall pain that caused a loss of rowing training time. Thirteen of these were confirmed to be bone stress by positive bone scan, while 15 were diagnosed as non bony chest wall pain, with many, but not all confirmed with a negative bone scan. The time cost of a bony injury is 4-5 times greater than non bony. Rib stress reactions generate an average of 47.8 days time lost and rib stress fractures 60.0 days time lost. In comparison with 12.6 days time lost with other chest wall pain. During the same time period, elite rowers presenting with chest wall pain were monitored at each treatment occasion for the presence of a number of subjective and objective markers. The subjective markers were night pain and pain on activities of daily living (e.g. opening a door, carrying a bag). The objective markers were pain response to deep breath, cough, push up and sit up. There are marked differences between the two groups in the onset, severity, number and longevity of these presenting signs that may allow the early differentiation of the two clinical entities. Conclusion: This information, plus the time frames captured by the injury surveillance system, has been used to generate a clearer picture of chest wall pain in rowers. It has enabled the development of a clinical management pathway to guide treating practitioners.